Prussian blue positive electrode material and preparation method thereof, positive plate, sodium-ion battery and power-related equipment
By pre-coated Prussian blue materials with sodium ferrocyanide and combined with carbon coating, the problem of easy collapse of the crystal structure of Prussian blue materials is solved, significantly improving the electrochemical performance and capacity retention rate of sodium ion batteries.
Patent Information
- Application Number
- CN202510062660.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-15
AI Technical Summary
The crystal structure of Prussian blue materials is prone to collapse, affecting the electrochemical performance of sodium ion batteries.
By mixing the Prussian blue material with sodium ferrocyanide in the first ball mill, a Prussian blue positive electrode material is formed with sodium ferrocyanide pre-coated, and in the second step, a secondary ball milling and calcination is performed with the carbon source to form a carbon-coated Prussian blue positive electrode material.
This method effectively prevents the material's lattice distortion, improves the stability and specific capacity of the material, and circulates for 1,000 cycles at a current density of 200mA/g, and the capacity retention rate exceeds 90%.
Smart Images

Figure CN119833618A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of new energy technology, and in particular to a Prussian blue positive electrode material and a preparation method thereof, a positive electrode sheet, a sodium ion battery and electrical equipment. Background Art
[0002] Sodium-ion batteries have become an important supplement to lithium-ion batteries in the fields of low-speed electric vehicles and energy storage due to their low cost, high and low temperature performance and excellent storage performance. Common sodium-ion battery positive electrode materials include Prussian blue analogs, but Prussian blue materials are prone to collapse due to the Jahn-Taylor effect of their own crystal structure, which affects the electrochemical performance of sodium-ion batteries. Summary of the invention
[0003] The purpose of the present application is to provide a Prussian blue-based positive electrode material and a preparation method thereof, a positive electrode sheet, a sodium ion battery and electrical equipment, aiming to solve the problem that the crystal structure of existing Prussian blue-based materials is prone to collapse, affecting the electrochemical performance of sodium ion batteries.
[0004] To achieve the above objectives, the present application provides a method for preparing a Prussian blue positive electrode material, comprising:
[0005] The Prussian blue material and sodium ferrocyanide are first ball-milled to obtain a first precursor;
[0006] The first precursor is subjected to a first calcination to obtain a Prussian blue positive electrode material pre-coated with sodium ferrocyanide.
[0007] In some embodiments, at least one of the following conditions is met:
[0008] A. The mass ratio of the Prussian blue material to sodium ferrocyanide is 1:(0.05-0.5);
[0009] B. The rotation speed of the first ball milling mixing is 600-800r / min;
[0010] C. The first ball milling mixing time is 30-60min;
[0011] D. Add ethanol to the first ball-milled mixture.
[0012] In some embodiments, at least one of the following conditions is met:
[0013] A. the temperature of the first calcination is 180-200°C;
[0014] B. the first calcination time is 2-4h;
[0015] C. the heating rate of the first calcination is 2-5°C / min;
[0016] D. The first calcination is carried out under a protective atmosphere.
[0017] In some embodiments, after obtaining the sodium ferrocyanide pre-coated Prussian blue cathode material, the method further comprises:
[0018] The sodium ferrocyanide pre-coated Prussian blue positive electrode material and the carbon source are mixed by a second ball milling process to obtain a second precursor;
[0019] The second precursor is subjected to a second calcination to obtain a carbon-coated sodium ferrocyanide pre-coated Prussian blue positive electrode material.
[0020] In some embodiments, at least one of the following conditions is met:
[0021] A. The mass ratio of the sodium ferrocyanide pre-coated Prussian blue positive electrode material to the carbon source is 1:(0.05-0.2);
[0022] B. The carbon source includes at least one of tannic acid, citric acid and ascorbic acid.
[0023] C. the temperature of the second calcination is 180-200°C;
[0024] D. the second calcination time is 6-8h;
[0025] E. The heating rate of the second calcination is 2-5°C / min.
[0026] In some embodiments, the chemical formula of the Prussian blue-based material is Na2MnFe(CN)6.
[0027] The present application also provides a Prussian blue positive electrode material, which is prepared by the above-mentioned method for preparing the Prussian blue positive electrode material;
[0028] Optionally, the Prussian blue-based positive electrode material is a sodium-rich Prussian blue-based material with an angular phase structure.
[0029] The present application also provides a positive electrode sheet, comprising the above-mentioned Prussian blue positive electrode material.
[0030] The present application also provides a sodium ion battery, comprising the above-mentioned positive electrode sheet.
[0031] The present application also provides an electrical device, comprising the above-mentioned sodium ion battery.
[0032] Compared with the prior art, the beneficial effects of this application include:
[0033] The preparation method of the Prussian blue positive electrode material provided in the present application uses sodium ferrocyanide to coat the Prussian blue material once. The melting point of sodium ferrocyanide is not fixed, starting from 82°C. First, it is evenly dispersed on the surface of the Prussian blue material by ball milling, and then after the first calcination, the sodium ferrocyanide is coated on the material by melt diffusion method. During ball milling and calcination, the ferrocyanide vacancies of the material can be effectively supplemented, and a coating layer is formed on the outer layer of the material to effectively prevent the lattice distortion of the material. Sodium ferrocyanide repairs the inherent defects of the Prussian blue positive electrode material, which can further improve its specific capacity while improving stability.
[0034] The Prussian blue positive electrode material provided in the present application has a specific capacity of up to 135.6 mAh / g at a current density of 200 mA / g, and a capacity retention rate of over 90% after 1000 cycles at a current density of 200 mA / g.
[0035] The sodium ion battery provided in the present application adopts the above-mentioned Prussian blue positive electrode material. In view of the advantages of the above-mentioned Prussian blue positive electrode material, the capacity and cycle performance are improved, and the electrochemical performance is excellent. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0037] Figure 1 A schematic flow chart of an embodiment of a method for preparing a Prussian blue cathode material of the present application;
[0038] Figure 2 A schematic flow chart of another embodiment of the method for preparing a Prussian blue positive electrode material of the present application;
[0039] Figure 3 This is the XRD result of the Prussian blue cathode material of Example 1;
[0040] Figure 4 The charge-discharge curve of the Prussian blue positive electrode material of Example 1 at a current density of 200 mA / g in the second cycle;
[0041] Figure 5 This is a cycle diagram of the first 150 cycles of the Prussian blue-based positive electrode material of Example 1 at a current density of 200 mA / g. DETAILED DESCRIPTION
[0042] As used herein:
[0043] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0044] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0045] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0046] In these examples, parts and percentages are by mass unless otherwise indicated.
[0047] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.
[0048] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0049] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0050] This application provides a method for preparing a Prussian blue positive electrode material. Figure 1 ,include:
[0051] S100: performing a first ball milling on a Prussian blue material and sodium ferrocyanide to obtain a first precursor;
[0052] S200: performing a first calcination on the first precursor to obtain a Prussian blue positive electrode material pre-coated with sodium ferrocyanide.
[0053] The preparation method of the Prussian blue positive electrode material provided in the present application uses sodium ferrocyanide to coat the Prussian blue material once. The melting point of sodium ferrocyanide is not fixed, starting from 82°C. First, it is evenly dispersed on the surface of the Prussian blue material by ball milling, and then after a first calcination, the sodium ferrocyanide is coated on the material by melt diffusion method. During ball milling and calcination, the ferrocyanide vacancies of the material can be effectively supplemented, and a coating layer is formed on the outer layer of the material, which effectively prevents the lattice distortion of the material.
[0054] In some embodiments, the mass ratio of the Prussian blue material to sodium ferrocyanide in step S100 is 1:(0.05-0.5), for example, it can be any ratio between 1:0.05, 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5 or 1:(0.05-0.5).
[0055] In some embodiments, the chemical formula of the Prussian blue-based material is Na2MnFe(CN)6.
[0056] In some embodiments, the rotation speed of the first ball milling mixing in step S100 is 600-800r / min, for example, it can be 600r / min, 650r / min, 700r / min, 750r / min, 800r / min or any value between 600-800r / min; the time is 30-60min, for example, it can be 30min, 35min, 40min, 45min, 50min, 55min, 60min or any value between 30-60min; ethanol is added to the first ball milling mixing.
[0057] In some embodiments, the temperature of the first calcination in step S200 is 180-200°C, for example, it can be 180°C, 185°C, 190°C, 195°C, 200°C or any value between 180-200°C; the time of the first calcination is 2-4h; the heating rate of the first calcination is 2-5°C / min; the first calcination is carried out under a protective atmosphere.
[0058] In some embodiments, see Figure 2 After obtaining the sodium ferrocyanide pre-coated Prussian blue positive electrode material, the method further comprises:
[0059] S300: performing a second ball milling mixing of the Prussian blue cathode material pre-coated with sodium ferrocyanide and the carbon source to obtain a second precursor;
[0060] S400: performing a second calcination on the second precursor to obtain a carbon-coated sodium ferrocyanide pre-coated Prussian blue positive electrode material.
[0061] The Prussian blue positive electrode material pre-coated with sodium ferrocyanide is then secondarily coated with a low-temperature cracking carbon source to obtain a double-coated Prussian blue positive electrode material; the role of carbon coating is to prevent the sodium ferrocyanide from being completely dissolved and released in the aqueous electrolyte, causing it to be unable to play a role, and secondly, to further prevent the lattice distortion effect of the material to form secondary protection.
[0062] Sodium ferrocyanide repairs the inherent defects of Prussian blue cathode materials, which can further improve their specific capacity while improving stability. At the same time, carbon coating increases their conductivity, which is beneficial to the transmission of electrons. In addition, the double coating strategy ensures that there will be no serious lattice distortion inside. In addition, the secondary calcination basically removes the crystal water, and sodium ferrocyanide fills the water vacancies, so that the stability and specific capacity of the material are greatly improved.
[0063] In some embodiments, the mass ratio of the Prussian blue-based positive electrode material pre-coated with sodium ferrocyanide to the carbon source in step S300 is 1:(0.05-0.2), for example, it can be any ratio between 1:0.05, 1:0.1, 1:0.15, 1:0.2 or 1:(0.05-0.2).
[0064] Too much carbon source leads to less active substances, which is not conducive to the performance of the material. Too little carbon source leads to poor coating effect and cannot stabilize the crystal structure.
[0065] In some embodiments, the carbon source in step S300 includes at least one of tannic acid, citric acid, and ascorbic acid.
[0066] In some embodiments, the temperature of the second calcination in step S400 is 180-200°C, for example, 180°C, 185°C, 190°C, 195°C, 200°C or any value between 180-200°C; the time of the second calcination is 6-8h; the heating rate of the second calcination is 2-5°C / min.
[0067] The present application also provides a Prussian blue positive electrode material, which is prepared by the above-mentioned method for preparing the Prussian blue positive electrode material;
[0068] Optionally, the Prussian blue-based positive electrode material is a sodium-rich Prussian blue-based material with an angular phase structure.
[0069] The Prussian blue positive electrode material provided in the present application has a specific capacity of up to 135.6 mAh / g at a current density of 200 mA / g, and a capacity retention rate of over 90% after 1000 cycles at a current density of 200 mA / g.
[0070] The present application also provides a positive electrode sheet, comprising the above-mentioned Prussian blue positive electrode material.
[0071] The present application also provides a sodium ion battery, comprising the above-mentioned positive electrode sheet.
[0072] The sodium ion battery provided in the present application adopts the above-mentioned Prussian blue positive electrode material. In view of the advantages of the above-mentioned Prussian blue positive electrode material, the capacity and cycle performance are improved, and the electrochemical performance is excellent.
[0073] The present application also provides an electrical device, comprising the above-mentioned sodium ion battery.
[0074] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0075] The preparation method of the Prussian blue material used in the following examples and comparative examples is as follows:
[0076] Take 3 mmol of MnSO4, 2 mmol of FeSO4, 5 mmol of sodium citrate, 2.5 mmol of sodium ascorbate, and 1 g of Na2SO4 respectively, and dissolve them in 20 ml of deionized water to form solution A.
[0077] Take 6mmol sodium ferrocyanide, 2g Na2SO4, 2.5mmol sodium ascorbate, and 10mmol sodium citrate, and dissolve them in 40ml deionized water to form solution B.
[0078] Solution A was gradually added dropwise to solution B at a constant flow rate (5 ml / min) using a peristaltic pump. After the addition was completed, solution C was obtained. Solution C was kept stirring continuously at a speed of 500 r / min for 12 h, and then aged for 24 h to obtain a white Prussian blue analog precipitate.
[0079] The white Prussian blue analog precipitate in solution C was filtered, and the original solution was filtered out, and then ethanol was added for washing. After being dried, the solution was taken out and placed in a vacuum drying oven, and dried at 120° C. for 12 hours to obtain a Prussian blue analog precursor.
[0080] Example 1
[0081] This embodiment provides a Prussian blue positive electrode material, and the preparation method thereof comprises the following steps:
[0082] Take 1g of the Prussian blue analog precursor and 0.1g of sodium ferrocyanide, mix them, add ethanol and perform ball milling, the ball milling time is 30min, the rotation speed is 600r / min. After drying, scrape out the powder, put the powder into a crucible, put it into a tube furnace, and calcine it in an argon atmosphere, the calcination temperature is 180℃, the time is 2h, the heating rate is 2℃ / min, and after cooling, the sodium ferrocyanide pre-coated Prussian blue analog is obtained.
[0083] The sodium ferrocyanide pre-coated Prussian blue analogue was mixed with 10%wt of tannic acid, ground evenly, and then placed in a tube furnace for secondary calcination at a calcination temperature of 180°C for 6 hours at a heating rate of 2°C / min to obtain the carbon-coated sodium ferrocyanide pre-coated Prussian blue cathode material of Example 1, whose XRD pattern is as follows: Figure 3 shown.
[0084] Example 2
[0085] This embodiment provides a Prussian blue positive electrode material, and the preparation method thereof comprises the following steps:
[0086] Take 1g of the Prussian blue analog precursor and 0.1g of sodium ferrocyanide, mix them, add ethanol and perform ball milling, the ball milling time is 30min, the rotation speed is 600r / min. After drying, scrape out the powder, put the powder into a crucible, put it into a tube furnace, and calcine it in an argon atmosphere, the calcination temperature is 180℃, the time is 2h, the heating rate is 2℃ / min, and after cooling, the sodium ferrocyanide pre-coated Prussian blue analog is obtained.
[0087] The sodium ferrocyanide pre-coated Prussian blue analogue was mixed with 5%wt of tannic acid, ground evenly and put into a tubular furnace for secondary calcination at a calcination temperature of 180°C for 6 hours at a heating rate of 2°C / min to obtain the carbon-coated sodium ferrocyanide pre-coated Prussian blue positive electrode material of Example 2.
[0088] Example 3
[0089] This embodiment provides a Prussian blue positive electrode material, and the preparation method thereof comprises the following steps:
[0090] Take 1g of the Prussian blue analog precursor and 0.1g of sodium ferrocyanide, mix them, add ethanol and perform ball milling, the ball milling time is 30min, the rotation speed is 600r / min. After drying, scrape out the powder, put the powder into a crucible, put it into a tube furnace, and calcine it in an argon atmosphere, the calcination temperature is 180℃, the time is 2h, the heating rate is 2℃ / min, and after cooling, the sodium ferrocyanide pre-coated Prussian blue analog is obtained.
[0091] The sodium ferrocyanide pre-coated Prussian blue analogue was mixed with 15%wt of tannic acid, ground evenly and placed in a tubular furnace for secondary calcination at a calcination temperature of 180°C for 6 hours at a heating rate of 2°C / min to obtain the carbon-coated sodium ferrocyanide pre-coated Prussian blue positive electrode material of Example 3.
[0092] Example 4
[0093] This embodiment provides a Prussian blue positive electrode material, and the preparation method thereof comprises the following steps:
[0094] Take 1g of the Prussian blue analog precursor and 0.05g of sodium ferrocyanide, mix them, add ethanol and perform ball milling, the ball milling time is 30min, the rotation speed is 600r / min. After drying, scrape out the powder, put the powder into a crucible, put it into a tube furnace, and calcine it in an argon atmosphere, the calcination temperature is 180℃, the time is 2h, the heating rate is 2℃ / min, and after cooling, the sodium ferrocyanide pre-coated Prussian blue analog is obtained.
[0095] The sodium ferrocyanide pre-coated Prussian blue analogue was mixed with 10%wt of tannic acid, ground evenly and placed in a tubular furnace for secondary calcination at a calcination temperature of 180°C for 6 hours at a heating rate of 2°C / min to obtain the carbon-coated sodium ferrocyanide pre-coated Prussian blue positive electrode material of Example 4.
[0096] Example 5
[0097] This embodiment provides a Prussian blue positive electrode material, and the preparation method thereof comprises the following steps:
[0098] Take 1g of the Prussian blue analog precursor and mix it with 0.15g of sodium ferrocyanide, add ethanol and perform ball milling, the ball milling time is 30min, the rotation speed is 600r / min. After drying, scrape out the powder, put the powder into a crucible, put it into a tube furnace, and calcine it in an argon atmosphere, the calcination temperature is 180℃, the time is 2h, the heating rate is 2℃ / min, and after cooling, the sodium ferrocyanide pre-coated Prussian blue analog is obtained.
[0099] The sodium ferrocyanide pre-coated Prussian blue analogue was mixed with 10%wt of tannic acid, ground evenly and placed in a tubular furnace for secondary calcination at a calcination temperature of 180°C for 6 hours at a heating rate of 2°C / min to obtain the carbon-coated sodium ferrocyanide pre-coated Prussian blue positive electrode material of Example 5.
[0100] Example 6
[0101] Embodiment 6 provides a Prussian blue positive electrode material, and the preparation method thereof comprises the following steps:
[0102] 1 g of the Prussian blue analog precursor was mixed with 0.1 g of sodium ferrocyanide, and ethanol was added for ball milling. The ball milling time was 30 min and the rotation speed was 600 r / min. After drying, the powder was scraped out, placed in a crucible, put into a tube furnace, and calcined in an argon atmosphere at a temperature of 180° C. for 2 h at a heating rate of 2° C. / min. After cooling, the sodium ferrocyanide pre-coated Prussian blue positive electrode material of Example 6 was obtained.
[0103] Comparative Example 1
[0104] The Prussian blue-based positive electrode material of Comparative Example 1 is the Prussian blue analog precursor prepared in the present application without any coating treatment.
[0105] Comparative Example 2
[0106] Comparative Example 2 provides a Prussian blue positive electrode material, and the preparation method thereof comprises the following steps:
[0107] The Prussian blue analog precursor was mixed with 10% wt of tannic acid, ground evenly and then placed in a tube furnace for calcination at a temperature of 180°C for 6 h at a heating rate of 2°C / min to obtain the carbon-coated Prussian blue cathode material of Comparative Example 2.
[0108] The Prussian blue positive electrode materials of Examples 1 to 6 and Comparative Examples 1 to 2 were respectively mixed with PVDF (polyvinylidene fluoride) and conductive carbon black at a mass ratio of 8:1:1 to prepare positive electrode sheets. First, the above materials were weighed in proportion and placed in a small weighing bottle (2.5cm*2.5cm), and a certain amount of NMP (N-methylpyrrolidone) solution was added dropwise, stirred for 6 hours, and the stirred slurry was coated on a stainless steel foil. After coating, it was placed in a vacuum drying oven and dried at 120°C for 8 hours, and then cut into small disc electrode sheets with a diameter of 16mm using a cutting machine, and compacted under a pressure of 10Mpa. Ensure that the mass of the Prussian blue analog active substance on this electrode is approximately 2.1mg cm -2 The above is done to obtain the positive electrode sheets of each embodiment and comparative example.
[0109] The preparation method of the negative electrode material used in this application is as follows: 2.0g NaH2PO2, 2.0g H3TiO3, and 2.0H3PO4 are added to 2.0ml deionized water, stirred at 800r / min for 5min to mix evenly, transferred to a 50ml high-pressure reactor, kept at 160℃ for 8h, the heating rate is 5℃ / min, centrifuged to obtain a white precipitate, and dried overnight at 60℃ in a vacuum drying oven to obtain a NaTi2(PO4)3 precursor. 2.0g of the prepared NaTi2(PO4)3 precursor and 0.1g of glucose are put into a mortar, 5ml of anhydrous ethanol solution is taken for grinding for 5-10min, then transferred to a ball mill jar, ball milled for 10-20min, the powder is taken out, placed in a vacuum drying oven, and carbonized at 600℃ for 6h at a heating rate of 5℃ / min, and finally a carbon-coated NaTi2(PO4)3 negative electrode material is obtained.
[0110] The preparation method of the negative electrode sheet is as follows: take the prepared carbon-coated sodium titanium phosphate, conductive carbon black, and PVDF (polyvinylidene fluoride) in a mass ratio of 7:2:1. First, weigh the above materials in proportion and place them in a small weighing bottle (2.5cm*2.5cm), add 17 drops of NMP (N-methylpyrrolidone) solution, stir for 4 hours, apply the stirred slurry on the copper foil, place it in a vacuum drying oven after coating, dry it for 8 hours, and then use a cutting machine to cut it into small disc electrode sheets with a diameter of 16mm, and compact it under a pressure of 10Mpa to ensure that the mass of the active material on this electrode is about 2.1mg cm -2 Make sure the capacity ratio of positive and negative electrodes is 1:(1.2-1.3) to get the negative electrode sheet.
[0111] Preparation of aqueous full battery: The full battery adopts 2016 button battery, and the installation order is negative electrode shell, spring, gasket, negative electrode plate, electrolyte (17m NaClO4), diaphragm (glass fiber diaphragm), electrolyte (17m NaClO4), positive electrode plate, gasket, positive electrode shell.
[0112] Full battery test: The charge and discharge cycle test is carried out on the Xinwei battery test system, with a test voltage range of 0.01-2.0V and a constant temperature of 25℃.
[0113] Figure 4 The charge-discharge curve of the Prussian blue positive electrode material of Example 1 at a current density of 200 mA / g in the second cycle is shown in FIG. Figure 4 1, 2, 3 are the number of cycles; Figure 5 This is a cycle diagram of the first 150 cycles of the Prussian blue-based positive electrode material of Example 1 at a current density of 200 mA / g.
[0114] The electrochemical performance results of the button-type full cells of Examples 1 to 6 and Comparative Examples 1 to 2 are shown in Table 1, and the mass percentage of the thermogravimetric water content is shown in Table 2.
[0115] Thermogravimetric water content analysis method: Under an inert atmosphere, heat the material to 500°C at a rate of 10°C / min, measure the mass loss of the material during the process, and obtain the weight loss rate, which can effectively characterize the adsorbed water and crystallized water content of Prussian blue cathode materials.
[0116] Table 1 Electrochemical performance of sodium ion batteries of various embodiments and comparative examples
[0117]
[0118]
[0119] Table 2 Thermogravimetric water content of the positive electrode materials of each embodiment and comparative example
[0120]
[0121] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
[0122] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. A method for preparing a Prussian blue positive electrode material, characterized in that: include: The Prussian blue material and sodium ferrocyanide are first ball-milled to obtain a first precursor; The first precursor is subjected to a first calcination to obtain a Prussian blue positive electrode material pre-coated with sodium ferrocyanide.
2. The method for preparing a Prussian blue positive electrode material according to claim 1, characterized in that: At least one of the following conditions is met: A. The mass ratio of the Prussian blue material to sodium ferrocyanide is 1:(0.05-0.5); B. The rotation speed of the first ball milling mixing is 600-800r / min; C. The first ball milling mixing time is 30-60min; D. Add ethanol to the first ball-milled mixture.
3. The method for preparing a Prussian blue positive electrode material according to claim 1, characterized in that: At least one of the following conditions is met: A. the temperature of the first calcination is 180-200°C; B. the first calcination time is 2-4h; C. the heating rate of the first calcination is 2-5°C / min; D. The first calcination is carried out under a protective atmosphere.
4. The method for preparing a Prussian blue positive electrode material according to claim 1, characterized in that: After obtaining the sodium ferrocyanide pre-coated Prussian blue positive electrode material, the method further comprises: The sodium ferrocyanide pre-coated Prussian blue positive electrode material and the carbon source are mixed by a second ball milling process to obtain a second precursor; The second precursor is subjected to a second calcination to obtain a carbon-coated sodium ferrocyanide pre-coated Prussian blue positive electrode material.
5. The method for preparing a Prussian blue positive electrode material according to claim 4, characterized in that: At least one of the following conditions is met: A. The mass ratio of the sodium ferrocyanide pre-coated Prussian blue positive electrode material to the carbon source is 1:(0.05-0.2); B. the carbon source comprises at least one of tannic acid, citric acid and ascorbic acid; C. the temperature of the second calcination is 180-200°C; D. the second calcination time is 6-8h; E. The heating rate of the second calcination is 2-5°C / min.
6. The method for preparing a Prussian blue positive electrode material according to any one of claims 1 to 5, characterized in that: The chemical formula of the Prussian blue material is Na2MnFe(CN)6.
7. A Prussian blue positive electrode material, characterized in that: Prepared by the preparation method of the Prussian blue positive electrode material according to any one of claims 1 to 6; Optionally, the Prussian blue-based positive electrode material is a sodium-rich Prussian blue-based material with an angular phase structure.
8. A positive electrode sheet, characterized in that: The invention comprises the Prussian blue positive electrode material as described in claim 7.
9. A sodium ion battery, characterized in that: Including the positive electrode sheet as claimed in claim 8.
10. An electrical equipment, characterized in that: Including the sodium ion battery as described in claim 9.